Слепой. Живая сталь: [роман] / Андрей Воронин - Воронин Андрей Николаевич (ACT, 2015)
Экземпляры: ф.9 (20161025) / Инвентарный номер: 53647 / Цена: / Сис.шифр: Р2 / Авт.знак: В 75 / ББК: 84(2Pос=Рус)6-44